Estimate of the subglacier dielectric constant of an ice shelf using a ground-penetrating step-frequency radar - Hamran, Svein Erik; Erlingsson, Bjørn; Gjessing, Yngvar; Mo, Per (IEEE Transactions on Geoscience and Remote Sensing, 1998)
The mass balance of the Antarctic ice cap, its stability, and the role of the surrounding ice shelf in bottomwater mass formation is, to a large extent, dictated by processes associated with subsurface freezing and melting, where the submerged ice meets the surrounding ocean. It is demonstrated how multifrequency ground-penetrating radar data collected at the Riiser-Larsenisen can be used to examine the physical conditions of the ice-shelf subsurface. The received radar signal from three different frequency intervals, 10-30, 155-170, and 330-360 MHz (range of wavelengths from 15 to 0.5 m in the ice), was analyzed by using a plane reflector model. It is demonstrated that the data can be successfully used to distinguish between types of ice at the ice-ocean interface, such as for freezing marine ice, melting marine ice, melting meteoric ice from the ice cap, and melting firn/ice. The data analysis shows that the subsurface can be regarded as rough on length scales in the order of 1 m.
Keywords: Antarktis; brehylle; fjernanalyse; geofysikk; georadar; glasiologi; isbreer; isbrem; isshelf; oseanografi

Stepwise Consolidation of Glacigenic Sediments Related to the Glacial History of Prydz Bay, East Antarctica - Solheim, Anders; Forsberg, Carl; Pittenger, Alan (Proceedings of the Ocean Drilling Program, 1991)
Keywords: Antarktis; glasiologi; isshelf; kontinentalsokkel

Field experiments on Antarctic tabular icebergs - Kristensen, Monica; Orheim, Olav; Wadhams, Peter (Polar Record, 1981)
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi; is; isfjell; isshelf; kalv; kalving

Physical characteristics and life expectancy of tabular Antarctic icebergs - Orheim, Olav (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; isfjell; isfront; isshelf; kalving; stratigrafi

Flow of Antarctic ice shelves between long. 29° E. and 44° W - Orheim, Olav (Journal of Glaciology, 1979)
Publisher: Cambridge University Press
Keywords: Antarktis; glasiologi; innlandsis; isfront; isshelf; isstrøm; kalving

Ice-shelf underwater morphology - Orheim, Olav (Journal of Glaciology, 1979)
Publisher: Cambridge University Press
Keywords: Antarktis; NARE 1976/77; ekspedisjoner; forskning; glasiologi; isshelf; morfologi

Hvorfor er de Antarktiske isfjell så store? - Orheim, Olav (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; glasiologi; innlandsis; isbreer; isfjell; isshelf; kalving; topografi

Thermohaline convection in the vicinity of an ice shelf - Foldvik, Arne; Kvinge, Thor (University of Bergen, 1974)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: AABW; Sørishavet; bunnvannet; ekspedisjoner; havis; isshelf; oseanografi; sjøis; sjøvann

Blue ice-fields, moraine features and glacier fluctuations - Schytt, Valter; Hisdal, Vidar (Glaciology II, 1961)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; brehylle; glasiologi; isbrem; isshelf

The inner structure of the ice shelf at Maudheim as shown by core drilling - Schytt, Valter; Hisdal, Vidar (Glaciology II, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; brehylle; glasiologi; isbrem; isshelf